Analysis of Variables That Influence Financing at Sharia Banks - Lukman, Lukman (PT Inovasi Pratama Internasional, 2025)
Financing plays an important role in improving the performance of Islamic banks. Financing indicators are commonly used to measure bank performance. Financing as the main source of bank profitability is carried out using the principle of prudence. To increase financing, continuous efforts are needed by increasing the allocation of larger financing in the future. A number of variables have an important role in improving financing performance, including savings, inflation and profit sharing. This research aims to analyze the influence of savings variables, inflation and profit sharing on financing at Sharia Banks. This research uses quantitative descriptive analysis methods. The research results show that simultaneously it is known that savings and inflation have a significant effect on financing at Sharia Banks. Meanwhile, the profit sharing variable has no effect on sharia bank financing. Partially, third party funds, inflation and profit sharing do not have a significant effect on financing at Sharia Banks. However, efforts are needed to maximize financing, especially in increasing competitiveness and improving bank performance in the future.